2008
DOI: 10.1111/j.1365-2133.2007.08415.x
|View full text |Cite
|
Sign up to set email alerts
|

U.K. consensus statement on the use of extracorporeal photopheresis for treatment of cutaneous T-cell lymphoma and chronic graft-versus-host disease

Abstract: Extracorporeal photopheresis (ECP) has been used for over 30 years in the treatment of erythrodermic cutaneous T-cell lymphoma (CTCL) and over 20 years for chronic graft-versus-host disease (cGVHD). The lack of prospective randomized trials has led to different centres having different patient selection criteria, treatment schedules, monitoring protocols and patient assessment criteria. ECP for CTCL and cGVHD is available only at six specialized centres across the U.K. In the recent Improving Outcomes Guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
2
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 77 publications
5
113
2
13
Order By: Relevance
“…Although the study did not meet its primary endpoint of total skin score (TSS) improvement, the patients in ECP arm did better in terms of steroid dose and TSS although not statistically significant. Other retrospective studies have shown benefit of ECP in treatment of cGVHD as well [106,128]. A study of 80 patients receiving two consecutive ECP treatments every 2 weeks showed that 84 % patients were able to complete 6 months of treatment and 50 % patients had reduction in symptoms [129], thus suggesting this probably is an effective regimen.…”
Section: Extracorporeal Photopheresis (Ecp) and Puvamentioning
confidence: 99%
“…Although the study did not meet its primary endpoint of total skin score (TSS) improvement, the patients in ECP arm did better in terms of steroid dose and TSS although not statistically significant. Other retrospective studies have shown benefit of ECP in treatment of cGVHD as well [106,128]. A study of 80 patients receiving two consecutive ECP treatments every 2 weeks showed that 84 % patients were able to complete 6 months of treatment and 50 % patients had reduction in symptoms [129], thus suggesting this probably is an effective regimen.…”
Section: Extracorporeal Photopheresis (Ecp) and Puvamentioning
confidence: 99%
“…Seventeen patients had oral disease. Other organs involved included liver (8), eyes (14), gut (7), lung (3) and muscles/joints (6).…”
Section: Demographicsmentioning
confidence: 99%
“…14 ECP was performed using the UVAR XTS or CELLEX photopheresis systems (Therakos, Ascot, UK). The technique has been described previously.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%
“…A UK consensus paper supported the findings and recommended ECP use in this group, with paired sessions every 2 weeks with reassessment at 3 months (Scarisbrick et al 2008).…”
Section: Second-line Third-line and Other Therapies For Chronic Gvhdmentioning
confidence: 82%